1997
DOI: 10.1007/s11746-997-0239-1
|View full text |Cite
|
Sign up to set email alerts
|

Facile purification of a C‐terminal extended His‐tagged Vibrio mimicus arylesterase and characterization of the purified enzyme

Abstract: lrlgliluI[.' [If B(atany, ,'M adernia Sinica, Nankang,1 ,'.iplg, raiv,,,u~ 11 ~2!l, drlr, J /'D(?raarml(,t11 i.~r St,lld lel/hr~ologv, Td.illl.,i, Ta!wan ]11 ABSTRACT: ViJlrio mimicu,~ arylesterase, a 20 kDa protein, is a nlultiiuln~ tifma] enzyme with Ihioe,qer,tse at:<] chyl~qntl-yl)sin-like activilies, gecaLise an aflinily His-tag ,:six consecutive his{idin0 affinily' tag:l clirectly, [o the prnh.qn cau,4~d Ihe loss of enzyllq[? aLtivity, a hr,.,xade(-a]X':l::.tide v,.,itl'. His-tag, A1)I'NSSSVf)K1.AAAL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…2), fails to exhibit enzyme activity (11). Previous work revealed that a hexadecapeptide spacer between the His-tag and C-terminus is needed to restore the enzyme functions of arylesterase (11). The recombinant thioesterase I constructed with the same spacer between the His-tag and the C-terminus resulted in an opposite result, i.e., this recombinant has no enzyme activity (data not shown).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…2), fails to exhibit enzyme activity (11). Previous work revealed that a hexadecapeptide spacer between the His-tag and C-terminus is needed to restore the enzyme functions of arylesterase (11). The recombinant thioesterase I constructed with the same spacer between the His-tag and the C-terminus resulted in an opposite result, i.e., this recombinant has no enzyme activity (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…The same man-ufactured protein of V. mimicus arylesterase, which shares a high amino acid sequence identity (51.7%) with the thioesterase I (Fig. 2), fails to exhibit enzyme activity (11). Previous work revealed that a hexadecapeptide spacer between the His-tag and C-terminus is needed to restore the enzyme functions of arylesterase (11).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation